A split‐label design for simultaneous measurements of perfusion in distant slices by pulsed arterial spin labeling. Issue 5 (9th June 2021) - Baligand, Celine; Hirschler, Lydiane; Veeger, Thom T. J.; Václavů, Lena; Franklin, Suzanne L.; van Osch, Matthias J. P.; Kan, Hermien E.
Abstract : Purpose: Multislice arterial spin labeling (ASL) MRI acquisitions are currently challenging in skeletal muscle because of long transit times, translating into low‐perfusion SNR in distal slices when large spatial coverage is required. However, fiber type and oxidative capacity vary along the length of healthy muscles, calling for multislice acquisitions in clinical studies. We propose a new variant of flow alternating inversion recovery (FAIR) that generates sufficient ASL signal to monitor exercise‐induced perfusion changes in muscle in two distant slices. Methods: Label around and between two 7‐cm distant slices was created by applying the presaturation/postsaturation and selective inversion modules selectively to each slice (split‐label multislice FAIR). Images were acquired using simultaneous multislice EPI. We validated our approach in the brain to take advantage of the high resting‐state perfusion, and applied it in the lower leg muscle during and after exercise, interleaved with a single‐slice FAIR as a reference. Results: We show that standard multislice FAIR leads to an underestimation of perfusion, while the proposed split‐label multislice approach shows good agreement with separate single‐slice FAIR acquisitions in brain, as well as in muscle following exercise. Conclusion: Split‐label FAIR allows measuring muscle perfusion in two distant slices simultaneously without losing sensitivity in the distal slice.